Encyclopedia of technology and innovation management - Narayanan, V. K. (Veekay); O'Connor, Gina Colarelli; Safari eBooks (Chichester : Wiley, 2010)
"A broadly encompassing encyclopedia on the emerging topic of technology, innovation and management (TIM), this volume covers a wide array of topics. We note that TIM is an emerging field and one that is interdisciplinary, incorporating strategy and entrepreneurship, economics, marketing, organizational behavior, organization theory, physical and life sciences, and even law. We strive to ensure that all of these disciplines are represented in this volume, and that their intersections are made clear. Entries are contributed by scholars from around the world who are leading experts in their respective topics. This volume is appropriate for scholars who are new to this particular field, as well as industry practitioners interested in understanding the state of knowledge in these specific areas. Entries may also serve as useful instructional materials, given their span of coverage as well as their currency"--Resource description page.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management -- Encyclopedias; Organizational change -- Encyclopedias; Electronic books